THE IMPACT OF INNOVATION ON PROMOTING REGIONAL ECONOMIC PERFORMANCE - Mansyur Asri; Ernawati Ernawati (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study examines the impact of innovation capability on regional economic performance in Indonesia. The analysis unit comprises 546 regions in Indonesia: 38 provinces and 508 regencies/cities. The analysis period is 2024. The research data is secondary data published by the National Research and Innovation Agency (BRIN). The data were processed using quantitative descriptive methods, using graphs, percentages, and frequency distributions. The results indicate that innovation capability plays a role in driving regional economic performance in Indonesia. The majority of regions have lower innovation capability, accompanied by lower economic stability. The regions have high innovation capability accompanied by high economic performance. Some regions experience less sustainable long-term economic performance, as indicated by a large gap between economic performance and innovation capability.